Research Advances on Human-Eye-Sensitive Long Persistent Luminescence Materials - Wang, Yuhua; Guo, Haijie (Frontiers in Chemistry, 2021)
Based on the actual application requirements of muti-color long persistent luminescence (LPL) materials, we highlight the recent developments in the last decade on human eyes sensitive LPL materials and try to make a full list of known LPL compounds possessing 400-600 nm wavelengths and the duration time longer than 10 h (>0.32 mcd/m²), which is more sensitive to the human eye in night vision and can be used throughout the night. We further emphasize our group research of novel LPL materials and the regulation of LPL color to enable a full palette. In the end, we try to summarize the challenges and perspectives of LPL materials for potential research directions based on our limited understandings. This review could offer new enlightenment for further exploration of new LPL materials in the visible light range and related applications.